Ferroelectric hysteresis behavior in 0-3 pzt-cement composites: Effects of frequency and electric field - Chaipanich A. (2014)
Lead zirconate titanate (PZT)-cement composites of 0-3 connectivity were produced and the effects of the frequency and electric field on the ferroelectric polarization-electric field (P-E) hysteresis of the composites were investigated. It was found that there was an increase in both the instantaneous remnant polarization (Pir) and coercive field (E ic) when the applied field increased. The instantaneous remnant polarization (Pir) was found to reduce when the frequency was increased. The ferroelectric hysteresis loops only existed when the composites were subjected to lower frequency; i.e. at 20 and 40 Hz. At higher frequency, the loops tended to stretch out, showing more of a lossy characteristic.